Multiple tumor types including leiomyoma and Wilms tumor in a patient with Gorlin syndrome due to 9q22.3 microdeletion encompassing the PTCH1 and FANC‐C loci. Issue 11 (7th October 2013) - Garavelli, Livia; Piemontese, Maria Rosaria; Cavazza, Alberto; Rosato, Simonetta; Wischmeijer, Anita; Gelmini, Chiara; Albertini, Enrico; Albertini, Giuseppe; Forzano, Francesca; Franchi, Fabrizia; Carella, Massimo; Zelante, Leopoldo; et al.
ABSTRACT Gorlin syndrome or nevoid basal cell carcinoma syndrome (NBCCS) is an autosomal dominant condition mainly characterized by the development of mandibular keratocysts which often have their onset during the second decade of life and/or multiple basal cell carcinoma (BCC) normally arising during the third decade. Cardiac and ovarian fibromas can be found. Patients with NBCCS develop the childhood brain malignancy medulloblastoma (now often called primitive neuro‐ectodermal tumor [PNET]) in 5% of cases. The risk of other malignant neoplasms is not clearly increased, although lymphoma and meningioma can occur in this condition. Wilms tumor has been mentioned in the literature four times. We describe a patient with a 10.9 Mb 9q22.3 deletion spanning 9q22.2 through 9q31.1 that includes the entire codifying sequence of the gene PTCH1, with Wilms tumor, multiple neoplasms (lung, liver, mesenteric, gastric and renal leiomyomas, lung typical carcinoid tumor, adenomatoid tumor of the pleura) and a severe clinical presentation. We propose including leiomyomas among minor criteria of the NBCCS. © 2013 Wiley Periodicals, Inc.